التأثير الديني للمعبودات المصرية والفينيقية في بلاد المغرب القديم: دراسة مقارنة بين الإله آمون والإلاهة تانيت - شيحي حكيمة (Universty Of El-oued جامعة الوادي, 2024)
الملخص: سلطت هذه الدراسة الضوء على المشهد الديني الغني والمعقد في بلاد المغرب القديم، الممتدة من غرب نهر النيل شرقاً إلى أعمدة هرقل غرباً، ومن البحر المتوسط شمالاً إلى الصحراء الكبرى جنوباً، في الفترة الزمنية الممتدة من العصر الحجري القديم الأوسط إلى سقوط قرطاجة (100.000ق.م–146م)، المتأثر بالثقافتين المصرية والفينيقية، التي ساهمت في تطور معتقدات وأساطير السكان الأصليين وطقوسهم جنبًا إلى جنب مع هذه التأثيرات الخارجية، مما أدى إلى ظهور نسيج روحاني متعدد الأوجه، فوجود الآلهة المصرية مثل آمون والآلهة الفينيقية مثل تانيت، إلى جانب الممارسات الدينية المرتبطة بها، يدل على التأثير العميق والدائم لهذه الحضارات في العادات والتقاليد الدينية للمنطقة، وتساهم هذه الدراسة المقارنة في فهم أعمق للتاريخ الديني للمنطقة، وتأكيد الترابط الذي حصل بين ثقافات البحر الأبيض المتوسط القديمة. Résumé : فرنسية أو انجلزية This study shed light on the rich and complex religious landscape of the ancient Maghreb, stretching from the west of the Nile River in the east to the pillars of Hercules in the West, and from the Mediterranean Sea in the north to the Sahara Desert in the south, in the time period from the Middle Paleolithic to the fall of Carthage (100,000 BC.A.D.-146 ad), influenced by the Egyptian and Phoenician cultures, which contributed to the development of indigenous beliefs, myths and rituals along with these external influences, giving rise to a multifaceted spiritual Tapestry, the presence of Egyptian gods such as Amun and Phoenician gods such as Tanit, along with associated religious practices, demonstrates the deep and lasting influence of these This comparative study contributes to a deeper understanding of the religious history of the region, and confirms the interconnection that took place between the ancient Mediterranean cultures.
أطروحة دكتوراه تخصص تاريخ بلاد المغرب القديم في العلوم الاجتماعية والانسانية
Keywords: المغرب القديم، نهر النيل، معتقدات، أساطير، طقوس، مصر، فينيقيا، قرطاجة، آمون، تانيت; ancient Morocco; Nile River; beliefs; legends; rituals; Egypt; Phoenicia; Carthage; Amun; Tanit